Closing the gap while standing still: clinimetric properties of a low-cost balance platform and a user-friendly app for posturography - Tom Vredeveld; John F. Stins; Annelies J. van Vliet; Vincent C.M. Tuinder; Stephan P.J. Ramaekers; Michel W. Coppieters; Annelies L. Pool-Goudzwaard (PeerJ)
Background The Wii Balance Board (WBB) is used as a rehabilitation tool for balance or strength interventions and posturography in balance tasks. Nonetheless, implementation of posturography using the WBB in a clinical setting is hampered by required technical skills for signal processing to obtain meaningful balance measures. Therefore, this study aims to evaluate the concurrent validity and test–retest reliability of a WBB to measure center of pressure (COP) parameters and to provide an easy-to-use web application to improve implementation of posturography in clinical practice. Methods A cross-sectional study was carried out including 30 healthy adults who performed repeated balance tasks including single and double leg standing still with eyes open or eyes closed. A WBB on top of a laboratory-grade force plate synchronously measured COP. Parameters based on COP displacement were calculated, including standard deviation of displacement, velocity, pathlength and 95% predicted ellipse area. Results The concurrent validity of the WBB to measure COP in quiet standing still tasks was excellent for all parameters (Intraclass Correlation Coefficient (ICC) > 0.900, p < 0.001), apart from medio-lateral velocity (ICC = 0.571, p = 0.090 to ICC = 0.711, p = 0.057). For the single leg balance tasks, across the two measurements, all WBB COP derived parameters showed excellent correlations with COP parameters derived from a laboratory-grade force plate (ICC > 0.95, p < 0.001). Test–retest reliability of the WBB was poor (ICC below 0.5) to occasionally good (ICC between 0.75 to 0.90) for the COP parameters from quiet standing balance tasks. Comparable reliability was found for the repeated measurements of single leg standing still. Power spectra analysis of both force plates revealed larger measurement error by the WBB in medio-lateral direction in tasks requiring minimal postural adjustments. Conclusion The WBB revealed excellent concurrent validity with a laboratory-grade force plate for balance tasks on a single leg or two legs for most COP parameters. The reliability was poor to moderate for most tasks, however comparable to the findings from the laboratory grade force plate. An open-source web application, employing R Shiny, was created to provide a tool to analyse COP parameters. Hereby, it was demonstrated that open-source scientific tools may help researchers to bridge the gap between scientific findings and clinical use of posturography.